Intestinal proline is a potential anti-allergy factor for allergy diagnosis and therapy - Ma, Jinya; Wang, Chong; Wang, Fangting; Zhang, Yong; Liu, Yinghua; Zhang, Jiachao; Gao, Zhongshan; Zhang, Yi; Xie, Hujun; Wang, Yanbo; Fu, Linglin (Frontiers in Nutrition, 2022)
Allergy has become a public health problem worldwide, but effective diagnostic and therapeutic approaches are limited currently. Amino acids are essential macronutrients that potentially participated in the allergy process. This work aimed to investigate whether amino acids can be applied as a mediator for allergy diagnosis and therapy. Two cohort studies were performed to investigate the correlation between fecal amino acids and allergy responses, and a spleen cell model was used to validate the role of amino acids in regulating allergy. In a cohort study with 193 volunteers, fecal proline was found to be negatively correlated with serum IgE, and detailed data analysis revealed that people with high-IgE-mediated allergy had decreased odds of high intestinal proline. In another cohort study with distinct allergic and non-allergic individuals, proline concentration was significantly lower in the allergic group. Daily diet and metagenomics analysis showed that the proline intake and microbiota amino acid metabolism were not significantly different, implying that the body's proline metabolism might be different between allergic and non-allergic individuals. Furthermore, the spleen cell model demonstrated that proline specifically targeted Th2 and Treg activity. Overall, this work revealed a tight correlation between gut proline and serum IgE, indicating proline as a promising biomarker and a potential therapeutic method for allergic diseases.